2016
DOI: 10.1152/ajprenal.00306.2015
|View full text |Cite
|
Sign up to set email alerts
|

The endothelial-to-mesenchymal transition and endothelial cilia in EPC-mediated postischemic kidney protection

Abstract: Renal ischemia induces peritubular capillary rarefication and fibrosis, with the latter partly resulting from the endothelial-to-mesenchymal transition (EndoMT). Endothelial cilia transmit blood flow-associated forces into the cell. Early endothelial progenitor cells (eEPCs) have been shown to protect mice from acute kidney injury in the short term. The aim of the present study was to analyze midterm consequences of eEPC treatment in the context of endothelial cilia and the EndoMT. Male C57/Bl6N mice were subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 35 publications
0
23
0
Order By: Relevance
“…Among those were melatonin [47], 8-O-cAMP [51], Bone Morphogenetic Protein-5 (BMP-5) [46], and Angiopoietin-1 [50] and -2 [49]. A more recent study showed that PACs administration post-AKI did not only prevent the kidney from acute loss of excretory function but also stabilizeed certain structural outcome parameters such as interstitial fibrosis and loss of peritubular capillaries [52]. PACs predominantly act by indirect mechanims, whereas ECFCs also operate as substitutes of damaged endothelial cells [37].…”
Section: Proangiogenic Cells (Pacs) and Endothelial Colony Forming Cementioning
confidence: 99%
“…Among those were melatonin [47], 8-O-cAMP [51], Bone Morphogenetic Protein-5 (BMP-5) [46], and Angiopoietin-1 [50] and -2 [49]. A more recent study showed that PACs administration post-AKI did not only prevent the kidney from acute loss of excretory function but also stabilizeed certain structural outcome parameters such as interstitial fibrosis and loss of peritubular capillaries [52]. PACs predominantly act by indirect mechanims, whereas ECFCs also operate as substitutes of damaged endothelial cells [37].…”
Section: Proangiogenic Cells (Pacs) and Endothelial Colony Forming Cementioning
confidence: 99%
“…Figure 2 summarizes the EndoMT analyzes. In addition, we quantified interstitial matrix deposition in all groups after masson trichrome staining as published previously [14,19]. Matrix accumulation did not significantly differ between the control and any of the respective postischemic groups or between ´IRI´ and one or more of the interventional groups.…”
Section: Early Mesenchymal Transdifferentiation Of Endothelial Cells mentioning
confidence: 98%
“…We previously discussed reduced endothelial alpha-Tubulin (aT) expression to reflect an endogenous process of self-defense [14]. It needs however to be mentioned that respective analyzes were performed several weeks after IRI (1, 4, and 6 weeks).…”
Section: Endothelial Alpha-tubulin Abundances Do Not Vary Early Aftermentioning
confidence: 99%
See 1 more Smart Citation
“…In an ischemic AKI model by Pastchan et al [74], systemic injection of early EPCs decreased serum creatinine and ameliorated interstitial fibrosis. Exposure of endothelial cells to early EPC supernatant led to decreased smooth muscle actin and tubulin expression.…”
Section: Epc Studies In Various Disease Modelsmentioning
confidence: 99%